New Myrtenal–Adamantane Conjugates Alleviate Alzheimer’s-Type Dementia in Rat Model - Stela Dragomanova; Maria Lazarova; Aldar Munkuev; Evgeniy Suslov; Konstantin Volcho; Nariman Salakhutdinov; Amina Bibi; Jóhannes Reynisson; Elina Tzvetanova; Albena Alexandrova; Almira Georgieva; Diamara Uzunova; et al. (Molecules, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disease associated with memory impairment and other central nervous system (CNS) symptoms. Two myrtenal–adamantane conjugates (MACs) showed excellent CNS potential against Alzheimer’s models. Adamantane is a common pharmacophore for drug design, and myrtenal (M) demonstrated neuroprotective effects in our previous studies. The aim of this study is to evaluate the MACs’ neuroprotective properties in dementia. Methods: Scopolamine (Scop) was applied intraperitoneally in Wistar rats for 11 days, simultaneously with MACs or M as a referent, respectively. Brain acetylcholine esterase (AChE) activity, noradrenaline and serotonin levels, and oxidative brain status determination followed behavioral tests on memory abilities. Molecular descriptors and docking analyses for AChE activity center affinity were performed. Results: M derivatives have favorable physicochemical parameters to enter the CNS. Both MACs restored memory damaged by Scop, showing significant AChE-inhibitory activity in the cortex, in contrast to M, supported by the modeling analysis. Moderate antioxidant properties were manifested by glutathione elevation and catalase activity modulation. MACs also altered noradrenaline and serotonin content in the hippocampus. Conclusion: For the first time, neuroprotective properties of two MACs in a rat dementia model were observed. They were stronger than the natural M effects, which makes the substances promising candidates for AD treatment.